Utilization of Digital Marketing for Micro, Small, and Medium Enterprises (MSMES) at Firefly Distro - Syah, Muhammad Fahmi Johan; Nadira, Khairani Rahma (Universitas Muhammadiyah Surakarta, 2022)
This study aims to describe the use of digital marketing on Firefly Distro. This type of research is qualitative with a case study design. Data collection techniques in this study were: observation, interviews and documentation. The validity of the data used triangulation techniques and sources. The data analysis technique used an interactive data analysis model, namely data collection, data reduction, data presentation and drawing conclusions. The object of this research was digital marketing Firefly Distro. While the subjects were admins, employees, and consumers of Firefly Distro. There were three sources in this study, namely admin, employees, and consumers. This research was conducted in Firefly Distro, Sukoharjo Regency, Central Java . The results of the research were: Firefly Distro has utilized various e-commerce and social media to reach its consumers. So that they can monitor, provide for the needs and wants of their potential customers, besides that, potential consumers are also easy to find and obtain product information by exploring the virtual world. Various kinds of Instagram features have also been utilized such as captions, hashtags, highlights, bios, stories, feeds, and reels . Through the use of social media, it has the potential to help the marketing process.